SPECIAL BONE MEAL PRODUK HIDROLISIS ALKALI PADA TULANG AYAM - Denny Rusmana; Rachmat Wiradimadja; Fitri Apriani Noor; Intan Mayasaroh; Wiwin Winarsih (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2016)
The study aims to determine the effect of some alkaline hydrolysis to decolagenation , Ca and P content of chicken bones to produce Special Bone meal. Research using experimental design completely randomized nested (6X2), which consists of factor A are the type of Alkali (filtrat Abu Sekam (FAS) 10%, FAS 20%, KOH 2% KOH 4%, NaOH 2%, and NaOH 4% ) and factor W is the immersion time (24 hours and 48 hours) with each treatment was repeated five. The results showed that the type of alkali significantly affect (p≤0.05) decolegenation, the content of Ca and P chicken bones, while the immersion time factor significantly affected (p≤0.05) decolagenation and P content of chicken bones, but not significantly affect (p>0.05) the Ca content of chicken bones. Special Products Bone Meal best chicken bone obtained from the hydrolysis of chicken bone by 4% NaOH with a soaking time of 48 hours. With the ability decolagenation 60 ± 1.82% and the content of Ca, P, respectively 25.59 ± 0.57%, and 12.57 ± 0.26%